KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DALAM MENYELESAIKAN SOAL CERITA PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL - Viana Anggraeni; Devi Nurul Yuspriyati; Luvy Sylviana Zanthy (IKIP Siliwangi, 2023)
This study aims to determine the mathematical problem solving ability of SMP class VIII students in solving story problems on the material of a two-variable linear equation system (SPLDV). This research is a qualitative descriptive study. The subjects in this study were 20 grade VIII students at SMP Negeri 2 Haurwangi. The data collection technique used a test technique in the form of descriptive questions, totaling 4 questions and each question representing each indicator of mathematical problem solving ability. The instrument used in this research is in the form of a test of mathematical problem solving ability on the material of linear equations of two variables. Based on the results of the study, the results of the mathematical problem solving ability of students who had low mathematical problem solving abilities were 8 students (40%), the category of moderate mathematical problem solving ability was 7 students (35%) and the category of high mathematical problem solving ability was 5 students (25 %). It can be concluded that the mathematical solving ability of SMP class VIII students in solving story problems on the material of linear equations of two variables is still relatively low.